HAZARDS OF MEDICAL GLAUCOMA THERAPY IN THE CATARACT PATIENT - Mandal, Govind Kumar; Roy, Pummy; Choudhary, Jagdish (Student's Journal of Health Research Africa, 2025)
Background Cataracts and glaucoma are major causes of vision impairment worldwide, particularly among seniors. These disorders often coexist due to risk factors like aging and ocular hypertension. Anti-glaucoma medications are the main way to lower intraocular pressure (IOP), but prolonged use can damage the ocular surface, lens, and tissues, which can complicate cataract formation, progression, and surgery. Objective: Examine the impact of long-term medical glaucoma treatment on cataract surgery outcomes, including preoperative status, intraoperative difficulty, and postoperative outcomes. Methods A total of 97 individuals with age-related cataracts and a history of chronic medical glaucoma therapy (≥6 months) were included. The eye exam included visual acuity, slit-lamp biomicroscopy, fundus evaluation, intraocular pressure measurement, gonioscopy, and ocular surface analysis. The classification, quantity, and duration of anti-glaucoma drugs were recorded. Intraoperative and postoperative issues occurred during phacoemulsification or SICS, as well as visual recovery. Results 58.8% of 97 patients received multiple anti-glaucoma medications, with 76.3% receiving treatment for over 12 months. Ocular changes included conjunctival hyperemia (47.4%), superficial punctate keratitis (28.9%), pseudoexfoliation (25.8%), and lens subluxation (11.3%). In the procedure, 19.5% had inadequate pupillary dilatation, 12.4% had zonular weakness, and 8.2% needed capsular tension rings. Postoperative inflammation and delayed epithelial repair were more common in multi-drug users. Despite significant BCVA improvement for most patients, 13.4% had inadequate recovery due to pre-existing optic nerve injury and surgical issues. Conclusion Long-term glaucoma treatment, particularly with multiple drugs, can harm ocular tissues and complicate cataract surgery. Conjunctiva, lens capsule, corneal epithelium, and zonular apparatus changes may increase surgical risk and postoperative recovery. These risks must be identified early for preoperative planning and patient consultation. Ophthalmologists must weigh the risks and benefits of prolonged topical anti-glaucoma treatment for cataract patients with glaucoma.